Evidence of the practice of self-medication with antibiotics among the lay public in low- and middle-income countries: A scoping review - Aslam, Adeel; Gajdács,, Márió; Zin, Che Suraya; Ab Rahman, Norny Syafinaz; Ahmed, Syed Imran; Muhammad, Zeeshan Zafar; Jamshed, Shazia Qasim (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The current scoping review is an attempt to explore the key reasons, determinants, patterns and prevalence related to self-medication with antibiotics (SMA) among the lay public. An online search was conducted using Google Scholar, Science Direct, ProQuest and PubMed. A two-phase mapping approach was used. In the first phase, studies were screened. In the second phase, the data were extracted from selected studies followed by the assessment of data quality. A total of 24 studies were included; 20 were cross-sectional, 3 were qualitative and one was observational. The most common indications were flu, cough, common colds, sore throat, diarrhea, toothache and fever. The most common determinants reported were past good experience and suggestions from friends or relatives. The use of SMA was observed to be more frequent in younger aged individuals belonging to low- or middle-income groups. The prevalence rate was reported to be high among the South Asian lay public and may be a major contributor to antibiotic resistance. In conclusion, this scoping review identifies a need for education campaigns and mass media campaigns to strengthen lay public awareness about the side effects and risks associated with SMA. In addition to this, there is a need to implement strict policies by government agencies to restrict over the counter availability of antibiotics.